The gas production, ruminal fermentation parameters, and microbiota in response to Clostridium butyricum supplementation on in vitro varying with media pH levels - Zhang, Meimei; Liang, Gege; Zhang, Xinlong; Lu, Xiaotan; Li, Siyao; Wang, Xu; Yang, Wenzhu; Yuan, Yuan; Jiao, Peixin (Frontiers in Microbiology, 2022)
The aim of this study was to investigate the gas production (GP), dry matter disappearance (DMD), fermentation parameters and rumen microbiota in response to Clostridium butyricum (CB) supplementation in batch culture using a high forage substrate. The doses of CB were supplemented at 0 (Control), 0.5 × 106, 1 × 106, and 2 × 106 CFU/bottle, respectively, at either media pH 6.0 or pH 6.6. The 16S rRNA high throughput sequencing was used to detect the microbiota of fermentation culture in control and 1 × 106 CFU/bottle after 24 h of incubation. The results showed that the GP (P < 0.001), DMD (P = 0.008), total volatile fatty acid (VFA) concentration (P < 0.001), acetate to propionate ratio (P < 0.001) and NH3-N concentration (P < 0.001) were greater at media pH 6.6 than pH 6.0. The linearly increased DMD (pH 6.0, P = 0.002; pH 6.6, P < 0.001) and quadratically increased butyrate proportion (pH 6.0, P = 0.076; pH 6.6, P < 0.053) and NH3-N concentration (pH 6.0, P = 0.003; pH 6.6, P = 0.014) were observed with increasing doses of CB. The Alpha diversity indexes of OTU number and Chao1 were higher (P = 0.045) at media pH 6.6 than pH 6.0, however, they were not affected by CB supplementation. The PCoA analysis (unweighted uniFrac) demonstrated that the clustering of bacterial microbiota of control and CB were distinctly separated from each other at media pH 6.0. At phylum level, the abundance of Bacteroidota (P < 0.001) decreased, whereas that of Firmicutes (P = 0.026) increased when the media pH elevated from 6.0 to 6.6. Supplementation of CB increased relative abundances of Rikenellaceae_RC9_gut_group (P = 0.002), Christensenellaceae_R-7_group (P < 0.001) and NK4A214_group (P = 0.002) at gunus level. Interactions between media pH and CB addition were observed for bacteria at both phylum and genus level. These results indicated that increasing the media pH level and CB supplementation increased in vitro rumen digestibility, and altered the ruminal fermentation pattern (by media pH) and microbiota.